Doped‐MoSe2 Nanoflakes/3d Metal Oxide–Hydr(Oxy)Oxides Hybrid Catalysts for pH‐Universal Electrochemical Hydrogen Evolution Reaction. Issue 27 (8th August 2018) - Najafi, Leyla; Bellani, Sebastiano; Oropesa‐Nuñez, Reinier; Ansaldo, Alberto; Prato, Mirko; Del Rio Castillo, Antonio Esau; Bonaccorso, Francesco
Abstract: Clean hydrogen production is highly promising to meet future global energy demands. The design of earth‐abundant materials with both high activity for hydrogen evolution reaction (HER) and electrochemical stability in both acidic and alkaline environments is needed, in order to enable practical applications. Here, the authors report a non‐noble 3d metal Cl‐chemical doping of liquid phase exfoliated single‐/few‐layer flakes of MoSe2 for creating MoSe2 /3d metal oxide–hydr(oxy)oxide hybrid HER‐catalysts. It is proposed that the electron‐transfer from MoSe2 nanoflakes to metal cations and the chlorine complexation‐induced neutralization, as well as the in situ formation of metal oxide–hydr(oxy)oxides on the MoSe2 nanoflakes' surface, tailor the proton affinity of the catalysts, increasing the number and HER‐kinetics of their active sites in both acidic and alkaline electrolytes. The electrochemical coupling between doped‐MoSe2 /metal oxide–hydr(oxy)oxide hybrids and single‐walled carbon nanotubes heterostructures further accelerates the HER process. Lastly, monolithic stacking of multiple heterostructures is reported as a facile electrode assembly strategy to achieve overpotential for a cathodic current density of 10 mA cm −2 of 0.081 and 0.064 V in 0.5m H2 SO4 and 1m KOH, respectively. This opens up new opportunities to address the current density versus overpotential requirements targeted in pH‐universal hydrogen production. Abstract : Doped‐MoSe2 nanoflakes/3d metal oxide–hydr(oxy)oxide hybrids, produced by cost‐effective synthesis and manufacturing, are investigated as efficient pH‐universal hydrogen evolution reaction (HER)‐electrocatalysts. Such electrocatalysts exhibit low overpotential at a cathodic current density of 10 mA cm ‐2 of 0.081 and 0.064 V in 0.5m H2 SO4 and 1m KOH, respectively, as well as promising electrochemical stability under HER‐operation, fulfilling the key‐requirements for practical applications.